The division of labour in science: the tradeoff between specialisation and diversity - De Langhe, Rogier (Journal of Economic Methodology, 2010)
Economics is a typical resource for social epistemology and the division of labour is acommon theme for economics. As such it should come as no surprise that the presentpaper turns to economics to formulate a view on the dynamics of scientific communities, with precursors such as Kitcher (1990), Goldman and Shaked (1991) andHull (1988). But although the approach is similar to theirs, the view defended isdifferent. Mäki (2005) points out that the lessons philosophers draw from economicscan go either way depending on the model chosen. Thus, the aims of this paper are (1)to illustrate this flexibility by proposing an alternative model which assumes increasingreturns to adoption in science rather than the decreasing returns present in theaforementioned contributions; and (2) to outline the implications of this view forscientific pluralism and institutional design.